IMPROVING GRADE X STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE PARAGRAPH THROUGH ANIMATION MOVIE - Andy Zulfadlan; Tina Mariany Arifin (Universitas Negeri Medan, 2013)
The objectives of this Classroom Action Research (CAR) was to discover the application of animation movie in writing a narrative paragraph of Grade X students State Islamic Senior High School (Madrasah Aliyah Negeri: MAN), Pematangsiantar. The study was conducted in two cycles, i.e. cycle I and II, following the four steps of CAR, are: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The Instruments used for qualitative data were: observations, diary notes, and interview. The writing test was used as quantitative data. The results of the data analysis showed that the teaching-learning process was satisfactory the mean of the orientation test score was 61.85 while the mean of students’ score in cycle I was 74.31 and cycle II 80.28 in conclusion, it can be said that animation movie has shown the students’ interest and Thus English teachers are suggested to apply media in the teaching-learning process.